Dose-response meta-analysis of arsenic exposure in drinking water and hypertension. Issue 3 (March 2021) - Amiri, Afsaneh; Mokhayeri, Yaser; Mohammadi, Rasool; Karami, Mohammad Amin; Ghaderpoori, Mansour; Kamarehie, Bahram; Jafari, Ali
Abstract: Background: Based on the cross-sectional and cohort studies, exposure to As via drinking water can cause hypertension. Methods: We searched PubMed, ISI WOS, and Scopus for relevant studies up to 1 January 2018 using related keywords. The meta-analysis was done on 10 studies (n = 28255) that report Odds Ratio for hypertension. The extracted ORs between As concentration and hypertension were pooled using random effect models. Study heterogeneity was analyzed using I 2 . Results: The estimated adjusted OR for association between As and hypertension was 1.44 (95% CI: 1.12, 1.84) with I 2 = 71%. Dose-Response analysis showed a linear relationship between As and hypertension (OR = 1.0008 95% CI: 1.0003, 1.001). In general, by increase of each unit in arsenic concentration, odds of the hypertension would increase as 0.08%. Conclusion: There was a significant relationship between As exposure and hypertension. Abstract : Arsenic, Meta-analysis, Health risk, Chronic exposure, Drinking water